2013
DOI: 10.1016/j.jneumeth.2013.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Sleep spindle detection through amplitude–frequency normal modelling

Abstract: h i g h l i g h t sAn automated model-based spindle detection algorithm is proposed. It models the amplitude-frequency spindle distribution with a bivariate normal distribution. It automatically adapts to each individual subject and derivation. It was tested in seven healthy children and six adult patients suffering from different pathologies, and performs similarly or better than sleep experts. Normal modelling enhances spindle detection quality compared to fixed amplitude and frequency thresholds. t r a c t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 45 publications
(81 reference statements)
5
74
0
Order By: Relevance
“…We believe that together with using the metrics proposed in [10] it is important to report the fraction of spindles detected in each stage of sleep as well to evaluate the performance of any spindle detection algorithm. 1 190 10 3 135 42 0 2 101 0 0 77 24 0 3 91 5 8 75 3 0 4 104 32 8 54 10 0 5 164 4 0 110 50 0 6 146 0 0 97 49 0 Total 796 51 19 548 178 0 Comparison of results against [10] and [13] (evaluated using the same dataset) shows superior sensitivity and similar specificty values. These are shown in Table III. V. CONCLUSION Identification of sleep spindles is an integral part of sleep staging.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…We believe that together with using the metrics proposed in [10] it is important to report the fraction of spindles detected in each stage of sleep as well to evaluate the performance of any spindle detection algorithm. 1 190 10 3 135 42 0 2 101 0 0 77 24 0 3 91 5 8 75 3 0 4 104 32 8 54 10 0 5 164 4 0 110 50 0 6 146 0 0 97 49 0 Total 796 51 19 548 178 0 Comparison of results against [10] and [13] (evaluated using the same dataset) shows superior sensitivity and similar specificty values. These are shown in Table III. V. CONCLUSION Identification of sleep spindles is an integral part of sleep staging.…”
Section: Resultsmentioning
confidence: 95%
“…It is a transient waveform with waxing-waning morphology and exhibits strong presence in stage 2 of NREM sleep (N2), although it may be present in N3 stage with a lower frequency of occurence. According to the American Academy of Sleep Medicine, a sleep spindle is defined as "a train of distinct waves with frequency [11][12][13][14][15][16] with a duration ≥ 0.5 seconds" [1]. An example of typical sleep spindles in stage 2 of NREM sleep is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of our method of analyzing EEG is in that we consider EEG signal as a composition of so-called wave trains. In contract to papers devoted to detecting wave trains of one or two specific types, such as alpha spindles [1] and sleep spindles [2,3,4,5,6,7], we analyze any kind of wave trains in a wide frequency area. The developed method differs from analogous method for detailed analysis of time-frequency dynamics of EEG [8] in that the statistical analysis of samples of wave trains and a new method for visualizing the results of the analysis are proposed.…”
Section: Introductionmentioning
confidence: 99%
“…A data-driven probabilistic approach was used by Babadi et al [11] that showed high detection accuracy. For detection of spindles in children [12] presented a method using Hilbert-Huang transform while [13] used amplitude-frequency normal modelling to detect spindles in both children and adults. In another method, Schönwald et al [14] evaluated the use of matching pursuit (MP) for spindle detection and achieved good results.…”
Section: Introductionmentioning
confidence: 99%